A case of generalized ostraceous psoriasis mimicking dermatitis neglecta - Bianca Angelina Macêdo do Nascimento; Alessandra Haber Carvalho; Carolina Moraes Dias; Thaiane Lima Lage; Clívia Maria Oliveira Carneiro; Maraya de Jesus Semblano Bittencourt (Sociedade Brasileira de Dermatologia, 2015)
AbstractLithium has been implicated in the exacerbation of pre-existing psoriasis, in the induction of psoriasis on previously uninvolved skin of psoriasis patients, and in the triggering of psoriasis for the first time in patients without a personal or family history. Lithium-induced psoriasis (and its resistance to treatment) is one of the major reasons for noncompliance in patients treated with lithium. We describe a male patient who developed generalized ostraceous psoriasis whose clinical appearance mimicked dermatitis neglecta, 10 months after starting therapy with lithium.